KEHIDUPAN KELUARGA COMMUTER MARRIAGE KECAMATAN TAPUNG KABUPATEN KAMPAR - Diana Mega Putri; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
At this time the fulfillment of economic needs continues to increase, especially for those who are married and have children. Meanwhile there are not many job vacancies and competition is getting harder. Therefore, there are some families who decide to make a living far from where they live. In general, family life will live together and spend days in the same place of residence, but for families who choose a commuter marriage, they will live differently from their spouse or child. Due to the increasing number of couples working together and jobs requiring different locations, they temporarily separated. Couples who undergo this relationship will certainly face domestic problems, in household life there are several functions that must be played properly in order to run in balance. In the family a habbit will appear, but all of that is not permanent. Especially for couples who already have children, they must be able to fulfill the function of being good parents for their children. This research will involve 5 informants, and is located in the Tapung sub-district, Kampar district. The method used is descriptive qualitative by observing and conducting in-depth interviews with 5 informants. The results of this study indicate that each family has their own way of living their household life and as parents they will do their best to meet the needs of their children. Then as a husband and wife they must build communication and trust in order to remain harmonious. Keywords: Family, Habitus, Commuter Marriage